On Time and Target: Evaluating Colonoscopy Performance and Learning Curves in Coloproctology Residents - Brandão, Juliana Chaves; de Castro Junior, Paulo Cesar; Marques, Ruy Garcia (Journal of Coloproctology, 2025)
Colonoscopy is an essential procedure in colorectal cancer screening and treatment, and high-quality exams are crucial for maximizing diagnostic efficacy. Technical proficiency in colonoscopy is a key factor for the quality of the procedures and, so, for patient safety. This study analyzes the colonoscopy learning curve of coloproctology residents, using cecal intubation time as a metric. Cecal intubation time was analyzed in 216 exams performed by first- and second-year coloproctology residents at a university hospital in Rio de Janeiro/RJ, over a period of 10 months. The results revealed a learning curve with a significant reduction in cecal intubation time over the course of the training, particularly in first-year residents, who began their training in an environment with more frequent exams. These results align with earlier studies, emphasizing the importance of repetitive practice for developing the technical skills needed for competent colonoscopy.The findings of this study demonstrate that conducting between 100 and 150 colonoscopies suggests a suitable benchmark for achieving competence in this procedure.
Keywords: colonoscopy; traineeship; academic training; colorectal surgery; colorectal cancer